Case Report: Thromboembolism and Hemorrhagic Pericardial Effusion—The Janus Face of Primary Pericardial Angiosarcoma - Chen, Fei F.; Jiang, Shu F.; Dong, Chang; Che, Ying; Du, Lin Y.; Li, Zhi Y.; Yang, Zhi Q.; Zhao, Yi C.; Liu, Ying (Frontiers in Cardiovascular Medicine, 2021)
Background: Primary cardiac angiosarcomas, especially those originating in the pericardium, are extremely rare and aggressive tumors with poor prognosis. These types of malignant tumors have diverse clinical presentations and are often masked by other comorbidities. Case Summary: Our hospital reported a 59-year-old woman who initially presented with pulmonary thromboembolism (PTE) and was subsequently treated with low-molecular-weight heparin. However, she experienced acute pericardial tamponade after anticoagulation therapy, where no obvious mass was primarily identified upon imaging, both in the pericardium or within the heart. Emergency pericardiocentesis and drainage were performed, where a total of 210 mL of bloody effusion was drained. Four months later, she was hospitalized with progressive hemoptysis and dyspnea. A large mixed mass occupying the right pericardium was later identified by coronary computed tomography angiography (CCTA). The mass was consistent with the right atrium, with heterogeneous thickened pericardium and localized moderate pericardial effusion. CCTA and positron emission tomography scans later showed metastases in both lungs and bilateral pleura. Nodules in hilar and mediastinal lymph nodes were also significant. Ultrasound-guided biopsy was performed, and the patient was ultimately diagnosed with an angiosarcoma based on final positive results for both CD31 and CD34 markers. The patient refused chemotherapy and passed away while waiting for her pathology results. The patient survived for 6 months since the first reported episode of PTE. Conclusions: Our case indicates that patients presenting with both embolism and hemorrhage should urgently be channeled to a clinical specialist to confirm any malignant etiology. This would be beneficial to confirm an early diagnosis and lengthen the duration of patient survival. However, the diagnosis of primary cardiac angiosarcoma is still challenging and requires multiple imaging modalities and biopsies in order to assist the accurate diagnosis of disease and achieve effective patient management.